Immunogenicity of plant‐produced porcine circovirus‐like particles in mice - Gunter, Cornelius J. (Plant Biotechnol J, 2019)
Porcine circovirus type 2 (PCV‐2) is the main causative agent associated with a group of diseases collectively known as porcine circovirus‐associated disease (PCAD). There is a significant economic strain on the global swine industry due to PCAD and the production of commercial PCV‐2 vaccines is expensive. Plant expression systems are increasingly regarded as a viable technology to produce recombinant proteins for use as pharmaceutical agents and vaccines. However, successful production and purification of PCV‐2 capsid protein (CP) from plants is an essential first step towards the goal of a plant‐produced PCV‐2 vaccine candidate. In this study, the PCV‐2 CP was transiently expressed in Nicotiana benthamiana plants via agroinfiltration and PCV‐2 CP was successfully purified using sucrose gradient ultracentrifugation. The CP self‐assembled into virus‐like particles (VLPs) resembling native virions and up to 6.5 mg of VLPs could be purified from 1 kg of leaf wet weight. Mice immunized with the plant‐produced PCV‐2 VLPs elicited specific antibody responses to PCV‐2 CP. This is the first report describing the expression of PCV‐2 CP in plants, the confirmation of its assembly into VLPs and the demonstration of their use to elicit a strong immune response in a mammalian model.